2020
DOI: 10.3389/fcell.2020.00503
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of lncRNA-Perturbed TLR-Signaling Network Identifies Novel lncRNA Prognostic Biomarkers in Colorectal Cancer

Abstract: Increasing evidence has suggested that long non-coding RNAs (lncRNAs) are critical regulators in the Toll-like receptors (TLR)-signaling network to modulate colorectal cancer (CRC) development and progression. However, the mechanism and clinical significance for lncRNAs regulating TLR signaling pathways in CRC remained largely unknown. In this study, we performed an integrative network analysis of transcriptomics by focusing on a lncRNA-perturbed TLR-signaling network, identifying 280 lncRNAs and 122 mRNAs. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Studies have reported that lncRNAs are abnormally expressed RNAs with more than 200 nucleotides, which play special roles in various diseases, especially malignant tumor formation [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported that lncRNAs are abnormally expressed RNAs with more than 200 nucleotides, which play special roles in various diseases, especially malignant tumor formation [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] .…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNA is a novel kind of noncoding RNA, which is at least 200 nucleotides in length. The lncRNAs may participate in the progression of various diseases, especially malignant tumors [12][13][14][15][16][17] . The lncRNAs, as important tumor gene regulators, effect tumor biological behavior, transcriptional regulation, and post-transcriptional regulation [18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…These highly competitive interactions that constitute a conservative and cancer-specific module [ 44 ]. Chu Y et al also found that lncRNA perturbed TLR signaling network performance can serve as a new lncRNA prognostic biomarker in colorectal cancer [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have provided evidence that several lncRNAs are involved in HDAC and TLR signaling and cancer pathways. Liu et al identified TLR-related lncRNAs, AP000696.1, LINC00689, LINC00900, and AP000487.1, that are associated with the overall survival of esophageal carcinoma [ 130 ], and Chu et al also reported three lncRNAs (MCHR2, AC011472.4, and AC063944.1) that regulate TLR signaling [ 131 ]. Moreover, the involvement of lncRNA H19 [ 132 ] and NEAT1 [ 127 ] in HDAC activity has been reported in association with cancer.…”
Section: Discussionmentioning
confidence: 99%